Effect of gadopentetate dimeglumine on bone growth in zebrafish caudal fins. (1st February 2023) - Tang, Rongbiao; Chen, Yi; He, Naying; Li, Yan; Jin, Zhijia; Chen, Ke-Min; Yan, Fuhua
Abstract: Compared with MR plain scanning, gadolinium (Gd)-enhanced MR scanning can provide more diagnostic information. Gadopentetate dimeglumine is generally used as an MR enhancement contrast agent in some countries. It is a member of linear Gd-based contrast agents (GBCAs) which are considered more likely to release free Gd ions (Gd 3+ ) than macrocyclic GBCAs. Gd 3+ is one of the most effective known calcium antagonists, and can compete with calcium ions (Ca 2+ ) in Ca 2+ -related biological reactions. In this study, animal models of tissue regeneration were established by cutting the caudal fins of zebrafish, and the models were exposed with gadopentetate dimeglumine solution for different immersion times of 1, 3, and 5 min. Three GBCA exposures per week were performed in the first 3 weeks of the follow-up time. Morphological parameters such as regenerative area (RA), bone density, bone thickness and regenerative bone volume (RBV) were quantified using a camera and synchrotron radiation micro CT. RA decreased as total Gd intake increased in both the female group (ρ = −0.784, P < 0.0001) and the male group (ρ = −0.471, P = 0.011). The bone density of the regenerated bone increased after Gd exposure in the treated groups. The morphology of the regenerated bone from the treated groups became shorter and thicker. Our results showed that gadopentetate dimeglumine had osteogenic toxicity in zebrafish. Highlights: Gadopentetate dimeglumine released free Gd 3+ from the chelating agent after use. Gd 3+ competed with Ca 2+ in Ca 2+ -involved biological reactions. The bone density of regenerative bone increased after Gd exposure in zebrafish. The regenerated bone from the exposed zebrafish became shorter and thicker.